THE ELABORATION AND THE EVALUATION OF THE ACCEPTABILITY OF THE FISH BURGER OF ACARÁ-AÇÚ (LOBOTESSURINAMENSIS) IN THE MACAPAENSE MARKET - AP, BRAZIL - Marilu Teixeira Amaral; Fredson Costa Rodrigues; Pauliana Leão de Souza; Érica Antunes Jimenez (Universidade do Estado do Rio de Janeiro, 2016)
The increasing consumer market requires innovative and quality products to respond to demand; thereby it is necessary that new experiments of new products are performed. Furthermore, a sensory analysis is a quick and an effective method to evaluate the acceptability of new food products.  Therefore, the present study sought to assess the degree of acceptance of the fish burger meat of Acará-açú in the Macapá market.  A sensory analysis was performed by 145 taste-testers, randomly selected and without prior training, of whom scored 6 parameters on a hedonic scale between 1 and 9, assigning score 1 for "extremely disliked" and 9 for "greatly enjoyed."  The following parameters were tested: taste, aroma, texture, color, salt content and general acceptance.  In addition, the taste-testers were asked to score the likelihood that they would purchase the food product if available.  The scores attributed by tasters ranged from 1 to 5, considering 1 for "I definitely would not buy the product" and 5 for "I would certainly buy the product." From the sensory characteristics observed in this study, we may conclude that the fish burger's sensory analysis showed acceptability index greater than 82% for all attributes and the purchase intention was confirmed by 80% of the attendees. The tallied scores averaged above 5 for each sensory parameter indicating that fish burger meat of Acará -açú taste-tested in the Macapa market received positive acceptance which Indicative of the viability of the production of this product and distribution in the food market. DOI: 10.12957/demetra.2016.18445